2002
DOI: 10.1523/jneurosci.22-08-03061.2002
|View full text |Cite
|
Sign up to set email alerts
|

ADP and AMP Induce Interleukin-1β Release from Microglial Cells through Activation of ATP-Primed P2X7 Receptor Channels

Abstract: P2X(7) is a subtype of ATP-gated channels that is highly expressed in astrocytes, microglia, and other immune cells. Activation of P2X(7) purinoceptors by ATP or 3'-O-(4-benzoyl)-benzoyl ATP (BzATP) induces the formation of cytolytic pores and provokes release of interleukin-1beta from immune cells. We investigated the actions of other endogenous nucleotides on recombinant and microglial P2X(7) receptors using electrophysiology, fluorescence imaging, and interleukin-1beta release measurement. We found that ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 52 publications
4
96
0
Order By: Relevance
“…In the dorsal root ganglia, P2X 7 receptor subunit expression was similarly localised to supporting cells, such as, Schwann cells, and this finding is supported by published data in other species [32,33]. Neuronal expression of P2X 1- Fig.…”
Section: Discussionsupporting
confidence: 85%
“…In the dorsal root ganglia, P2X 7 receptor subunit expression was similarly localised to supporting cells, such as, Schwann cells, and this finding is supported by published data in other species [32,33]. Neuronal expression of P2X 1- Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Although the endogenous expression of P2Y 2 Rs has been reported in mouse microglia [67,214], it seems likely that increased levels of proinflammatory cytokines should further increase P2Y 2 R expression in glial cells in vivo. Our recent in vitro data show that treatment of mouse primary oligomeric/oligomeric Aβ 1-42 upregulates P2Y 2 R expression [145] via a pathway likely involving P2X7R-mediated IL-1β release [16,75,105,[154][155][156]. It also has been determined that P2X7R activation increases P2Y 2 R expression in rat astrocytes [215].…”
Section: P2y 2 Rs In Cns Inflammationmentioning
confidence: 95%
“…Indeed, it has been shown that the P2Y 2 R promoter contains a NF-κB binding sequence that is required for inflammation-induced P2Y 2 R upregulation, a pathway that can be blocked by Bay-11-7085, a specific inhibitor of the phosphorylation of IκB-α, the endogenous regulator of NF-κB activity [104]. Thus, it seems likely that the co-release of IL-1β and nucleotides mediated by ATP-induced P2X7R activation in microglia [16,75,105] provides an in vivo mechanism for both the upregulation and activation of P2Y 2 Rs in neurons and other cell types. ATP release also occurs from activated microglia and astrocytes under oxidative stress [15] and following neuronal excitation [17,106] via volume-activated anion channels [106], P2X7Rs [107], and pannexin hemichannels [37,108] or upon exposure to fibrillar or oligomeric Aβ [14,75,109].…”
Section: P2y 2 Receptor Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rat growth plate chondrocytes express P2X 2 and P2X 5 receptors (154), raising the possibility that articular chondrocytes express a subset of P2X receptors. Another P2X receptor, P2X 7 , is required for IL-1 maturation and release from macrophages (155), microglia (156), and endothelial cells (157). Chondrocytes release IL-1␤ and may therefore express P2X 7 .…”
mentioning
confidence: 99%